Literature as a tool of national education: Rahman Shaari’s insights into Malaysian national identity - Jamin, Asyraff; Subet, Mary Fatimah (Intelektual Pustaka Media Utama, 2026)
Literature always played an important role in shaping societies, cultures, and nations. As a powerful tool for the transmission of ideas, values, and experiences, literature can serve as an educational medium, particularly for fostering national consciousness. Therefore, this study aims to identify, evaluate, and understands the role of literature as a tool of national education in raising national consciousness and shaping national identity. This qualitative study employs content analysis and library research methods based on Lukacs’ theory of realism, to examine Rahman Shaari’s perspectives on national identity in his novels Pernikahan di Lubuk Hantu, Semoga Molek, and Cengkaman Hasrat. The findings show that Rahman Shaari’s works truly emphasize efforts to educate society towards preserving and promoting Malaysian National Identity. His discourse on elevating Bahasa Melayu and preserving Malaysia’s cultural heritage underscores his commitment to national identity. The study concludes that Rahman Shaari’s portrayal of national identity is aligns with the realities of Malaysian society and Lukacs’ aesthetic principles, positively impacting and demonstrating the role of literature as an effective tool for national education. Subsequently, this study could serve as a resource for future studies specifically on how literature worldwide influences national identity across diverse societies.